Comprehensive analysis of salivary protein N-glycosylation for biomarker discovery and investigation of novel therapeutics in oral cancer - SINEVICI, NICOLETA (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
Oral Cancer (OC) is one of the few life threatening conditions of the oral cavity. There is an increasing number of cases in younger adults and women in particular; this is in contrast to the historical higher prevalence normally observed in older males. Despite the visibility of the oral cavity, late diagnosis of OC is common, and has one of the highest morbidity and mortality rates of all cancers. Surgical excision is the most effective treatment and is often combined with chemotherapy and/or radiotherapy, although these show only modest improvements in survival. Late stage diagnosis is attributed to the asymptomatic nature of the disease in its early stages and patients’ reticence to consult with a medical professional until the tumour becomes symptomatic. Early diagnosis and treatment would significantly reduce mortality from OC. Therefore, the option of utilising a biomarker to signal the early stages of the disease would be of immense benefit. Despite the extraordinary large number of potential candidate biomarkers, to date, there remains ambiguity and controversy as to their diagnostic potential. The potential convenience of saliva as a source of biomarkers in physiological and pathophysiological states, forms a solid platform for its clinical utility. Studies on glycosylation alterations have demonstrated their regulatory role in cancer development and progression, opening areas for biomarker discovery and therapeutic targets (Pinho and Reis, 2015). Therefore, the high content of glycoproteins in saliva makes this biofluid an obvious object for further investigation with regard to its diagnostic capabilities in OC. This is the first study to fully characterise the salivary glycome. To determine if salivary N-glycans have biomarker potential in OC a variety of techniques, including Hydrophilic Interaction Liquid Chromatography, coupled with sub 2 μm UPLC analysis, exoglycosidase digestions and Mass Spectrometry were employed. It was demonstrated that saliva contains a highly abundant and complex N-glycomic profile. Of the identified structures, the most prevalent were neutral in charge followed by smaller proportions of monosialylated and disialylated structures, with most structures showing different levels of fucosylation. Further analysis using isotopic labelling demonstrated both quantitative and qualitative changes within the salivary glycome. From the myriad of potential differences between the healthy salivary N-glycome and that of patients with different levels of dysplasia/OC, a number of glycan structures have been identified as putative biomarkers. The complexity of OC, modest response to current chemotherapeutics as well as the increased observation of resistance to current chemo/radiotherapeutics in OC (da Silva et al., 2012, Lee et al., 2013), particularly in patients suffering a recurrence, highlight a status quo that limits the ability of successfully treating OC. These issues also demonstrate that a ‘one for all’ chemotherapeutic is unlikely to have effective results in all patients, supporting a personalised OC treatment strategy. Since the serendipitous discovery of Bovine/Human α-lactaluminin Made Lethal to Tumour (BAMLET/HAMLET) there has been an increased interest in understanding the ability of α- lactalbumin to form a cytotoxic complex. The extensive literature on the complex, demonstrates both the in vitro and in vivo tumouricidal activity, in many different cancers and pathologies. This study demonstrates, for the first time, that BAMLET has the potential to disrupt dysplastic as well as oral cancerous cells, suggesting a novel use in OC. BAMLET utilises a combination of cell death mechanisms, including apoptosis and autophagy, exhibiting a significantly lower EC-50 in dysplastic cell lines. This suggests that BAMLET may be a useful treatment for oral dysplasias. The different effective doses between the two cancer cell lines tested, indicate that its efficacy may be patient dependent supporting its potential in personalised medicine. Collectively, the results presented in this thesis demonstrate the complexity of the salivary glycome and biomarker potential of salivary N-glycans in the diagnosis of dysplasia and OC. The identification of a non-toxic alternative to chemotherapy is also an exciting development and may lead to improved outcomes and quality of life (QOL) for patients should clinical trials be undertaken in the future. The novel findings presented in this work have expanded the boundaries of research into OC. Several new research opportunities are posed which will enhance the current knowledge base in OC through the search for both novel biomarkers and novel treatments. Future investigations in these areas will potentially lead to the implementation of point of care diagnostic tests in general practice to address the issue of late diagnosis. Improved survival and QOL for OC patients may also be achieved through the availability of alternative chemotherapeutic strategies.
APPROVED
Keywords: biomarkers, saliva, N-glycans, oral cancer